The blank space on the map - Minster, Jonathan (Department of English Language and Literature, 2015)
From the cold shores of Marion Island to the plains of the Great Karoo, this is a story about four South Africans, by birth or circumstance, who are marooned on the outskirts of society and trying to find their way back. Livhu is a scientist who has been sent to a remote research station to study ocean currents. Besides the challenge of adjusting to the frozen island landscape, she also grapples with her feelings for a young seal researcher. When the relationship takes an unwanted turn, Livhu is forced to search deep inside herself and find the strength to survive a lonely year very far from home. Casper is a sub-editor who works for the most trashy tabloid in Johannesburg. He’s on cruise control, plugging away at a job he doesn’t really enjoy, full of regret about previous opportunities he thinks he’s squandered. When a strange assignment comes his way, and a new friend with it, he sees the hazy outline of a map that will lead him away from previous hurt towards a brighter, more ambitious future. Garrick is a ski-boat skipper from Durban. He once captained cargo ships, but when his family fell apart and the rum took over, this was the only job he could get. Now he has a rare opportunity to make good money delivering a catamaran to the Seychelles and rekindle the bond with his estranged son at the same time. On the open ocean, however, tempers fray under skies brimming with thunderclouds, and the threat of pirates is ever present. Jamal walked out of war-torn Somalia as a teenager with his brother. Now his brother has been killed in a xenophobic attack in a Johannesburg township and Jamal is all alone. With no other prospects, he carries on walking, south towards Cape Town, where he has a cousin who might be able to help him. Along the way, desperate and dehydrated, he is taken in by an elderly loner in a small Karoo town who has secrets of his own. Unbeknownst to each other, the lives of these four strangers will touch each other in unexpected ways, suggesting that we are all closer than we’d like to admit, held together by the universal desire for redemption.